Application of block matrix theory to obtain the inverse transform of the vector-valued DFT - Soto-Quiros, Pablo (Hikari Ltd., 2015)
We study the vector-valued discrete Fourier transform (vector-valued DFT) and its inverse transform, the vector-valued DFT inversion, through its block matrix representation. These transforms are defined for N- periodic signals, taking values in CD. The vector-valued DFT is a gen- eralization of classical discrete Fourier transform definition. The goal of this paper is present necessary and sufficient new conditions to vector- valued DFT inversion, and so, to make a perfect recovery of original signal.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84929903975&partnerID=40&md5=6e63d2349064a8ba147c960968f44c64
Keywords: Vectores; Número de Fourier; Transformaciones de fourier; Transformada rápida de fourier; Research Subject Categories::MATHEMATICS::Applied mathematics